STAD Learning Model Assisted by 3D Natural Features Learning Media on the Cognitive Competence - Ni Kadek Michella Devayani; Kadek Suranata; I Gusti Agung Ayu Wulandari (International Journal of Natural Science and Engineering, 2026)
The low cognitive competence in Science and Social Studies (IPAS) among elementary school students remains a significant issue, primarily caused by teacher-centered instruction, limited variation in teaching methods, and the minimal use of concrete learning media. These conditions make it difficult for students to understand abstract concepts, particularly those related to natural landscape features. This study aimed to examine the effect of the Student Teams Achievement Divisions (STAD) learning model assisted by 3D Natural Landscape Features learning media on students' cognitive competence in IPAS. The study employed a quantitative approach using a quasi-experimental pretest–posttest control group design. The participants were fourth-grade elementary school students assigned to an experimental group and a control group. Data were collected through multiple-choice tests and analyzed using descriptive and inferential statistics. The results revealed a significant difference in mean scores between the experimental group (85.5) and the control group (67.2), indicating a substantial improvement in the cognitive competence of students who received instruction through the STAD learning model supported by 3D Natural Landscape Features learning media. The mean difference of 18.3 points reflects a meaningful academic gain, suggesting that the instructional intervention had a strong positive impact on students’ mastery of IPAS concepts. It can be concluded that the STAD learning model assisted by 3D Natural Landscape Features learning media is effective in enhancing the cognitive competence of elementary school students in IPAS learning.